ENDODONTIC EMERGENCIES IN PERMANENT DENTITION: A RETROSPECTIVE ANALYSIS OF 314 CASES AT THE UNIVERSITY TEACHING HOSPITAL OF KINSHASA, DR CONGO - Sofi NK; Songo B F; Kiyombo M; Adou M; Agbor M (Romanian Society of Oral Rehabilitation, 2020)
Background: Awareness of the consequences and complications of dental extractions has prompted many patients recently to seek endodontic treatment in order to conserve their teeth. The objective of our current study was to draw up the epidemiological and clinical profile of patients received for endodontic emergencies at the dental clinic of the University teaching hospital of Kinshasa, Democratic Republic of Congo (DRC). Methods: This was a cross-sectional descriptive study using patients records and a convenience sampling technique. the study was carried out at the Department of Dentistry of CUK (University of Kinshasa Teaching Hospital) between January 1994 to December 2013 for emergency endodontics. A data capture sheet containing variables of interest was used to collect the data from the patients records. Data was statistically analysed by the SPSS 20.0 software. Results: A total of 314 patients were recruited in the study. The majority of the patients were females (63.4 %). The predominant (46.3 %) age group was between 16 and 25 years. The frequency of preoperative endodontic emergencies was 88.5%. The posterior dental segments of the dental arcades were the most affected. Two-thirds (65.0 %) of the patients presented with dental caries in the acute pulpitis stage. Treatment included dental pulpectomies with antiseptic solution (66.2 %). Self-medication concerned was observed in 43.9 % of the files of the patients consulted while conservative treatments were discontinued by 65.6 %. Conclusion: The frequency of endodontic emergencies was high. The majority of the patients presented with acute pulpitis and self-medication was mostly used. This study highlights the need for strengthening oral health education on preventive measures concerning dental caries and its complications. The regulations on the dispensing of medicines must be strictly applied. The CUK Operative Dentistry Department need to upgrade its technical platform.